ANALISIS PERBANDINGAN NOVEL “MUTIARA DI KOTA MELBOURNE ” DAN “FOUR SEASONS IN BELGIUM” DENGAN PENDEKATAN MIMETIK - Seles, Susi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Comparative literature is interesting to observe. The use of a mimetic approach may indicate an art of presentation or imitation, implying something static; mimetic involves something dynamic, a process, an active relationship with the reality of life. The purpose of this study to find out how the comparison of the novel